Variability of Spatter Morphology in Pyroclastic Deposits in Southern Idaho, as Correlated to Thermal Conditions and Eruptive Environment. Issue 10 (13th October 2018) - Rader, E.; Kobs Nawotniak, S.; Heldmann, J.
Abstract: To investigate the thermal conditions of spatter eruptions on Earth, other planets, and moons we measured and categorized the physical characteristics of clasts in spatter deposits in Southern Idaho, USA. Physical characteristics of clasts, such as aspect ratio and degree of welding, are influenced by the style of eruption, distance from the vent, and lava properties. The correlation between morphological characteristics and the degree of fusion constrains thermal conditions of unwitnessed spatter‐producing eruptions on Earth and extraterrestrial volcanoes. We categorize spatter deposits into three groups, as defined by their emplacement conditions: primary vent, distal (spatter exposed in noneruptive cracks on the flanks of primary vents), and hornito (secondary spatter from a nonprimary cone); and show the variability of clast morphology within the three categories. Primary vent deposits typically show a wide range of fused perimeters between clasts (18–82%), lower aspect ratios (0.20–0.49), and larger void space, both between clasts (4–21%) and within clasts (referred to as hollow cores, up to 93%). Hornitos typically have less fusion (14–22%) between clasts, higher aspect ratios (0.45–0.49), and lower proportions of void space (6–10%). Distal outcrops are easily distinguished by the lack of void space (<8%) and the very high aspect ratio of clasts (close to 1). When chemical composition and outcrop proximity are accounted for, the accumulation rate appears to be primarily responsible for spatter clast morphology. Our results are based on field measurements of clasts; however, digital imagery could be used to categorize and interpret pyroclastic deposits in planetary systems by robotic spacecraft. Plain Language Summary: The way spatter deposits look (clash shape, size, etc.) changes with temperature. Hotter deposits from close to the vent can be distinguished from cooler deposits emplaced far from the heat source. This may have implications for using volcanic deposits to detect different eruption environments. Key Points: Study catalogs pyroclast size and morphology on a variety of spatter features Thermal conditions of deposition are reflected in the fusion between clasts as well as the degree of elongation of the clasts Spatter erupted in cooler environments (secondary spatter) may show different clast morphology (size, shape, and amount of fusion between clasts) than primary vent spatter